(untitled) (Journal of Science and Technology, 2016)
Europe, having condemned traditional African wood carvings for five centuries, turned back and acknowledged the same objects as ingenious works of arr. The carvings were acknowledged because the conditions which influenced their condemnation had largely changed.’ slavery had been abolished and Africans and their carvings had gained respect: traditions, conservatism, complacency and ethnocentrism had relaxed Europe had understood the symbolic nature of the carvings and had recognized their aesthetic qualities. Encouraged by anthropological writings, aesthetic, art and scholastic revolutions, and as a testimony of her acknowledgement, Europe acquired myriad’s of the sculptures for study, pleasure and exhibition; and demonstrating their acknowledgement, many European artists adopted the style of the carvings and copied samples of the figures into their art works.